1992
DOI: 10.1111/j.1365-4362.1992.tb03522.x
|View full text |Cite
|
Sign up to set email alerts
|

Porokeratosis of Mibelli Following Heart Transplant

Abstract: A 59-year-old white man with a history of Sydenham's chorea received a mitral valve prosthesis in 1962. He sustained an anterolateral myocardial infarction in 1983. In 1984, he received a heart transplant. To prevent heart rejection, he was initially treated with cyclosporine 12 mg/kg/day and prednisone 90 mg b.i.d. In 1987, azathioprine 100 mg daily was added. In 1989, at the time of our evaluation, his medications included cyclosporine 80 mg b.i.d., prednisone 10 mg b.i.d., and azathioprine 75 mg/day. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…5 Immunosuppression may be a factor in the extension or onset of DSAP. [9][10][11][12][13][14][15][16] It is proposed that immunosuppressants, which would include ultraviolet (UV) light and chemotherapeutic agents, promote porokeratosis via impairment of the Langerhans cells' immune surveillance function. 9 A role for UV light in the pathogenesis of DSAP is supported by the fact that fair-skinned individuals are most commonly affected; lesions rarely arise in dark-skinned individuals who have natural protection against sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…5 Immunosuppression may be a factor in the extension or onset of DSAP. [9][10][11][12][13][14][15][16] It is proposed that immunosuppressants, which would include ultraviolet (UV) light and chemotherapeutic agents, promote porokeratosis via impairment of the Langerhans cells' immune surveillance function. 9 A role for UV light in the pathogenesis of DSAP is supported by the fact that fair-skinned individuals are most commonly affected; lesions rarely arise in dark-skinned individuals who have natural protection against sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression might aid in the phenotypic expression of disseminated superficial actinic porokeratosis, and perhaps superficial disseminated porokeratosis and other forms of PK, in genetically predisposed individuals by two proposed mechanisms: (i) directly triggering expression of an abnormal clone of keratinocytes (4,5); or (ii) disrupting growth dynamics in the epidermis which promotes the proliferation of an abnormal clone. 4 , 5 , 6 It is thought that immunosuppressive drugs and ultraviolet light promote the development of PK in renal allograft patients by decreasing the density and impairing the immune surveillance function of epidermal Langerhans cells. 1 , 3 , 7 There is further speculation that epidermal Langerhans cells in PK have defective expression of HLA‐DR antigens which results in failure of their immunosurveillance function and aids in the development of abnormal clones of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Reed and Leone [20]have suggested that in a genetically predisposed individual, the disease results from the proliferation of abnormal clones of epidermal cells, which may be triggered by several stimuli, including sunlight or artificial UV light [18, 21, 22], exposure to electron beam radiotherapy [23], immunosuppressive treatments (as e.g. chemotherapy, immunosuppressive drugs or systemic corticosteroids) [4, 5, 6, 7, 8, 9, 10]or HIV infection [11]. A pathogenetic relationship between a latent virus infection and porokeratosis has been hypothesized, although never demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore clinical surveillance of patients is indicated when there is a history of intense sun exposure, X-ray irradiation or immunosuppressive disorders [4, 6, 18, 19, 21, 24, 25, 26, 27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation